2019
DOI: 10.1101/634642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discrete Community Assemblages Within Hypersaline Paleolake Sediments of Pilot Valley, Utah

Abstract: Hypersaline paleolake sediments are understudied ecosystems whose microbial ecology is largely unknown. Here we present mineralogical, geochemical, and small-subunit 16S rRNA gene sequence data on one such environment, the Pilot Valley Basin (PVB), a sub-basin of ancient Lake Bonneville located in northwest Utah. PVB exhibits a variety of aqueous minerals including phyllosilicates, carbonates, and sulfates, as well as microbially-induced sedimentary structures. As perchlorate occurs naturally (up to 6.5 ppb) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 79 publications
2
4
0
Order By: Relevance
“…The archaeal and bacterial taxa composition varies with sediment depth and mineralogy but is remarkably consistent across a horizontal transect of several kilometers ( 10 ). Similar microbial diversity results have been reported for hypersaline sediments in the nearby Pilot Valley basin, another remnant of Lake Bonneville, which has also been studied as a Mars analog environment due to its deposits of perchlorate ( 11 , 12 ).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The archaeal and bacterial taxa composition varies with sediment depth and mineralogy but is remarkably consistent across a horizontal transect of several kilometers ( 10 ). Similar microbial diversity results have been reported for hypersaline sediments in the nearby Pilot Valley basin, another remnant of Lake Bonneville, which has also been studied as a Mars analog environment due to its deposits of perchlorate ( 11 , 12 ).…”
Section: Introductionsupporting
confidence: 81%
“…Microbial diversity studies of these arid to hyperarid, hypersaline systems have confirmed the presence of resident microbial communities with both cultivation-dependent and cultivation-independent studies ( 10 , 19 , 20 ). A few studies have investigated these systems for their abilities to support specific metabolic activities, such as carbon monoxide oxidation ( 20 , 21 ), perchlorate reduction ( 12 ), and hypolithic photosynthesis ( 22 ).…”
Section: Introductionmentioning
confidence: 67%
“…The archaeal and bacterial taxa composition varies with sediment depth (spanning a few centimeters) but is remarkably consistent across a horizontal transect of several kilometers (McGonigle et al, 2019). Similar microbial diversity results have been reported for hypersaline sediments in the nearby Pilot Valley basin, another remnant of Lake Bonneville (Lynch et al, 2019b(Lynch et al, , 2019a.…”
Section: Introductionsupporting
confidence: 79%
“…The taxonomy of MAGs containing denitrification genes have been previously described as highly abundant organisms at BSF through 16S rRNA analyses (eg. Salinivenus, Halobacteriales, Nanosalinales, Halanerobiales, and Thiohalorhabdaceae) (Lynch et al, 2019b;McGonigle et al, 2019). While numerous MAGs contained genes for denitrification, none contained genes for all four steps in the process.…”
Section: Denitrification Is the Center Of The Bsf Nitrogen Cyclementioning
confidence: 99%
“…Only one culture-independent study of microorganisms at the BSF has been conducted previously (39). This study focused on the adjacent basin Pilot Valley but also included one sampling location at the BSF.…”
Section: Discussionmentioning
confidence: 99%